Kajian program bina syasiah staf di IPTAa: kajian kes di UTM & USM - Ripin, Mohd. Nasir; Suratman, Azmishah; Awang, Ramli; Sayed Ahmad, Sayed Mahussain; Haron, Zulkiflee (UTM, 2003)
This research studies on the programme of bina sahsiah among staf in Institution of Higher Learning (IPT) in order to identify form of implementation of the programme, to analyse the contents of the programme and to identify problems faced by the IPTs in implementing the programme. The study is done at Universiti Teknologi Malaysia and Universiti Sains Malaysia as a case. Data is collected by method of interview to the organiser of the programme as sampling of the study and then qualitatively analysed by the researcher. The results show that the IPTs nearly implement the programmes in the same content as well as face the similar problems. The study looks for suggestions in the final chapter.